Psychofarmacology in the prevention of somatic comorbid diseases in mentally ill patients - Jukić, Vlado, liječnik (Array, 2009)
In this paper a comparison is made between schizophrenia and somatic comorbidity before the era of antipsychotics and after, with consideration to the prevalent morbidity during each of these periods. In the period before antipsychotics acute infectious diseases and TBC were the prevalent comorbid diseases. High comorbidity rates were due not only to epidemics but also poor treatment success, deficient health habits and poor personal hygiene. Studies show that new generation antipsychotics partly generate the occurrence of metabolic disorders, which makes it necessary to consider the choice of antipsychotic depending on the assessed risk in every individual case.